Combined use of body condition score, radiography, ultrasonography and computed tomography in body condition evaluation of crab-eating fox (Cerdocyon thous) - Ferro, Barbara Sardela [UNESP]; da Silva, Jeana Pereira [UNESP]; Testa, Carolyne Assis Eigenheer Pinke [UNESP]; Corrêa de Camargo, Gabriel [UNESP]; Ichikawa, Ricardo Shoiti [UNESP]; Beltrán Urrego, Ana Camila [UNESP]; Guimarães-Okamoto, Piscylla Tatiana Chalfun [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Melchert, Alessandra [UNESP] (Springer Nature, 2024)
This study aimed to evaluate the application of radiography, ultrasonography, and computed tomography (CT) as auxiliaries in the determination of body fat and musculature in crab-eating foxes (Cerdocyon thous). Eight animals were evaluated and classified based on the body condition score (BCS) scale. The total cut volume, total visceral volume, total subcutaneous volume, visceral fat volume, subcutaneous fat volume, and total fat volume were measured. The correlation of the BCS with the other data was determined. In the ultrasound, there was a correlation of the vertebral epaxial musculature score (VEMS) with body weight, BCS, muscle mass score (MMS), animal's height, and height at the withers. In the radiographic analysis, the amount of subcutaneous fat obtained in L3 vertebrae did not present a significant correlation with BCS, as opposed to L6. In the tomographic analysis, TFV/L6, VFV/L6, and SFV/L6 correlated with BCS in L3, and only SFV /L6 in L6. When the ratios between fat volumes were correlated, the correlation with BCS occurred only in L6 in the TFV/TBV, SFV/SVC, and VFW variants. Radiography and CT were effective and had a good association with BCS. With the CT it was possible to demonstrate the distribution of total fat at the level of the L3 slice. The ratio of calculations considering the length of the L6 vertebra was more adequate, while at the level of L6 the ratio between the volumes of the compartments was more effective.
Keywords: Body fat; Body score condition; Imaging diagnosis; Wild-dog